REACH: Extending reality for distributed collaborative making - Casey Smith; Mike Tissenbaum (Computers & Education: X Reality, 2025)
Makerspaces allow students to engage in 21st-century skills such as critical thinking, collaboration, and problem-solving through construction and sharing of projects that are personally meaningful. Based in constructivist and socio-cultural learning theories, these student-centered spaces support learners in a community of practice as they construct knowledge through shared work with peers. However, uneven access to local expertise and peer support can make equitable participation in maker activities challenging. In an effort to expand the benefits of co-located making to interactions at a distance, this study investigates the collaborative affordances of a camera-projector device, REACH (Remote Embodiment for Augmented Collaborative Help) that augments user's workspaces through projection of artifacts for shared viewing and gesturing. This technology enhances the physicality of learning across distances, allowing students to discuss, adjust, and explore artifacts together without a common physical space. REACH's innovative approach to gesture-driven collaboration supports cognitive and communication processes, allowing students to deepen their understanding through remote yet tangible interaction. This aligns with ongoing educational reform efforts to adapt teaching practices and tools to address the complexities of remote and digital learning, ultimately enhancing access to the benefits of making.